DIFFERENCES ON ANTHROPOMETRIC MEASUREMENTS OF THE HAND BASED ON LATERALITY IN SERBIAN CONTEXT - Spasojević-Brkić, Vesna K; Brkic, Aleksandar; Veljkovic, Zorica; Perisic, Martina (Journal of Applied Engineering Science, 2020)
Anthropometric data are essential for designers of products, while hand anthropometric measurements are of special importance due to the fact that grasp enables different manipulation tasks. Literature review shows that differences on anthropometric characteristics of the hand based on laterality in Serbian context have not been examined till now, so this study tested it on the sample containing 110 subjects - 23 left-handed and 87 right-handed. Hand anthropometric measurements include 30 anthropometric dimensions measured on each examined participant. Dimensions are taken by capturing the imprints of the subjects’ outstretched hands. Collected data were subjected to descriptive statistics, t-test, Kolmogorov test and Mann-Withney U* tests. Also, 5th and 95th percentiles are calculated on all dimensions. Results show that there are no statistically significant differences based on laterality in Serbian context. Accordingly, hand tools and many other equipment, which are controlled by means of Serbian operator could be designed in the same manner both for workers whose dominant had is left and right. Also, percentiles values are calculated and should be taken into account in design processes. It is recommended, in future research to enlarge sample, repeat statistical testing and analyze hand grasp possible issues.
Keywords: hand, anthropometric measurement, left-handed, right-handed, statistical analysis